MOTIVASI ORANG TUA MENYEKOLAHKAN ANAKNYA DI PENDIDIKAN DINIYAH TAKMILIYAH AWALIYAH (PDTA) AL FIKRIYAH DI KELURAHAN PESISIR KECAMATAN LIMA PULUH KOTA PEKANBARU - Maemunaty, Titi; ', T Wilona; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the types of motivation parents educate their children in Pendidikan Diniyah Takmiliyah Awaliyah (PDTA) Al Fikriyah di Kelurahan Pesisir Kecamatan Lima Puluh Kota Pekanbaru seen from motivation. Because motivation was an impulse that there are on a person for act in achieving a particular goal. Formulation problems research is whether motivation parents educate their children in Pendidikan Diniyah Takmiliyah Awaliyah (PDTA) Al Fikriyah di Kelurahan Pesisir Kecamatan Lima Puluh Kota Pekanbaru?. And will the most dominant motivation of motivation intrinsic with the motivation extrinsic parents educate their children in Pendidikan Diniyah Takmiliyah Awaliyah (PDTA) Al Fikriyah di Kelurahan Pesisir Kecamatan Lima Puluh Kota Pekanbaru?. The purpose of this research is to find motivation parents educate his son Pendidikan Diniyah Takmiliyah Awaliyah (PDTA) Al Fikriyah di Kelurahan Pesisir Kecamatan Lima Puluh Kota Pekanbaru. Population in this study 90 parents. Then the researcher determine samples from 47 people for research and 20 people to the tests of somewhere else, with uses the technique of proporsionate stratified random sampling. An instrument data collection namely poll with 55 a statement and if the trial live 52 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. So, a conclusion can be drawn, motivation parents educate their children in Pendidikan Diniyah Takmiliyah Awaliyah (PDTA) Al Fikriyah di Kelurahan Pesisir Kecamatan Lima Puluh Kota Pekanbaru within high.Key words: Motivation, Motivation Parents Educate Their Children